PELAKSANAAN TUGAS KEPALA DESA DI DESA SUNGAI JALAU KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Riza Fitri; Harapan Tua (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Execution Of Duty Lead In Desq River of Jalau District OfCamphor North of Kabupaaten Camphor. Target of this research is to knowexecution of duty lead countryside in river countryside of jalau district of northcamphor of camphor sub-province and also factors what is is resistor of execution ofduty lead countryside [in] river countryside of jalau district of north camphor ofcamphor sub-province. To analyse phenomenon in this research of writer use theoryof Winardi with indicator exploiting of right time, amount of output, readiness towork along, quality of work. Metedologi which is used in this research is research ofresearch qualitative. Result of this research show Pelaksnaan duty lead countryside inCountryside River of Jalau District Of Camphor North Sub-Province Camphor stillnot yet is optimal. Factors Adapaun the found is human being sumberdaya, facilitiesand basic facilities, and also factor of society.Keyword : Execution Of Duty, Head Countryside